Comparative analysis of erythrocyte hemolysis, plasma parameters and metabolic features in red crucian carp (Carassius auratus red var) and triploid hybrid fish following Aeromonas hydrophila challenge. Issue 118 (November 2021) - Xiong, Ning-Xia; Luo, Sheng-Wei; Fan, Lan-Fen; Mao, Zhuang-Wen; Luo, Kai-Kun; Liu, Shao-Jun; Wu, Chang; Hu, Fang-Zhou; Wang, Shi; Wen, Ming; Liu, Qing-Feng
Abstract: Aeromonas hydrophila can pose a great threat to survival of freshwater fish. In this study, A. hydrophila challenge could promote the erythrocyte hemolysis, increase free hemoglobin (FHB) level and generate malondialdehyde (MDA) production in plasma but decrease the levels of total antioxidant capacity (T-AOC), total superoxide dismutase (SOD), catalase (CAT), alkaline phosphatase (ALP) and lysozyme (LZM) of red crucian carp (RCC, 2 N = 100) and triploid hybrid fish (3 N fish, 3 N = 150) following A. hydrophila challenge. Elevated expression levels of heat shock protein 90 alpha (HSP90α), matrix metalloproteinase 9 (MMP-9), free fatty acid receptor 3 (FFAR3), paraoxonase 2 (PON2) and cytosolic phospholipase A2 (cPLA2) were observed in A. hydrophila- infected fish. In addition, A. hydrophila challenge could significantly increase expressions of cortisol, leucine, isoleucine, glutamate and polyunsaturated fatty acids (PUFAs) in RCC and 3 N, while glycolysis and tricarboxylic acid cycle appeared to be inactive. We identified differential fatty acid derivatives and their metabolic networks as crucial biomarkers from metabolic profiles of different ploidy cyprinid fish subjected to A. hydrophila infection. These results highlighted the comparative metabolic strategy of different ploidy cyprinid fish against bacterial infection. Highlights: Erythrocytes of triploid cyprinid fish exhibited a higher resistance against A. hydrophila -induced hemolysis. Acute A. hydrophila infection could dramatically decrease antioxidant status in different ploidy cyprinid fish. Acute A. hydrophila infection could trigger the difference in fatty acid derivatives in different ploidy cyprinid fish.